(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The objective of the paper is insight on the Constitution of India is based on the principles of Ideals of Preamble, liberty, equality, fraternity and justice. As During the French Revolution the people got the idea from French Revolution , Liberty, fraternity, and equality and several Indian leaders were inspired by French and Russian Revolution. . For achieving aim we have undertaken a concise study of several journals and the books which are linked with the provisions of the Constitution manifest great respect for human dignity, commitment to equality and non-discrimination and concern for the weaker section in society. Further, the Constitution makes it mandatory for the Government to protect and promote freedoms and to assure every citizen a decent standard of living. In other words, the Indian Constitution guarantees the basic rights to every citizen of India Which are Claims of a person over other fellow being ,over the Society, over the government and recognized by the society ,sanctioned by the Law. . This paper dealt with general Constitutional Laws of India and the amendments made into Constitution of India. The paper tells us about the schemes for realization of the above mentioned goals are contained in the Fundamental Rights enshrined in the Constitution Part III and Part IV . The Right to Equality, The right to freedom, the right against exploitation, the right to freedom of religion, cultural and educational rights, right to constitutional remedies and special provisions relating to certain classes are some of the constitutional provisions ensuring human rights.